(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The existing methods (design directory) recommend using nomograms depending on the eccentricity of bending moment and numbers of piles while acting only vertical loads. These methods have a number of shortcomings and are inconvenient, because of lack of adequate alternatives and they do not provide the greatest efficiency. The convenient method of pile foundation designing (grillages and fields), depending on the load values, is the foundation proposed by the authors in this article. The results of numerical investigations determined the optimal grillages dimensions and numbers of pile in "bush" of pile, showed that this method gives optimal options for pile foundation under single column with large bending moments and minimum material expenditures and also provides its bearing capacity